2012
DOI: 10.1103/physreva.85.043803
|View full text |Cite
|
Sign up to set email alerts
|

Collapse-revival dynamics and atom-field entanglement in the nonresonant Dicke model

Abstract: We consider the dynamics of atomic and field coherent states in the non-resonant Dicke model. At weak coupling an initial product state evolves into a superposition of multiple field coherent states that are correlated with the atomic configuration. This process is accompanied by the buildup and decay of atom-field entanglement and leads to the periodic collapse and revival of Rabi oscillations. We provide a perturbative derivation of the underlying dynamical mechanism that complements the rotating wave approx… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The system-wide entanglement is dramatically enhanced over the static or adiabatic QPT values. Our results extend current understanding of coupled light-matter systems beyond the equilibrium ground state [2,[14][15][16][17], and also they also stand apart from more recent studies of out-ofequilibrium critical behavior [3,[5][6][7][8][9]18]. Moreover, our fully quantum analysis covers all dynamical regimes from very slow adiabatic through to sudden quench, capturing at each stage the emergent non-linear self interactions * ol.acevedo53@uniandes.edu.co and correlations within and between each subsystem.…”
Section: Introductionsupporting
confidence: 76%
“…The system-wide entanglement is dramatically enhanced over the static or adiabatic QPT values. Our results extend current understanding of coupled light-matter systems beyond the equilibrium ground state [2,[14][15][16][17], and also they also stand apart from more recent studies of out-ofequilibrium critical behavior [3,[5][6][7][8][9]18]. Moreover, our fully quantum analysis covers all dynamical regimes from very slow adiabatic through to sudden quench, capturing at each stage the emergent non-linear self interactions * ol.acevedo53@uniandes.edu.co and correlations within and between each subsystem.…”
Section: Introductionsupporting
confidence: 76%
“…Previous works on non-equilibrium DM under different settings have also confirmed that some major phenomena present here, such as spin squeezing, survive losses. Enhanced superradiance can be detected [36], and squeezing can still have time to develop [18,24]. We note that, despite perturbing the…”
Section: Scaling and Robustness Of Non-equilibrium Quantum Correlatiomentioning
confidence: 99%
“…Some previous works have already examined the dynamical emergence of quantum effects on each subsystem of the DM. However they focused on the semi-classical limit and a static coupling after a sudden quench [23][24][25][26], small dynamic oscillations around a phase space region [14], or under time-delayed feedback control [27]. Our work goes beyond this by giving a fully quantum analysis of the process of continuously turning on the interaction, in order to assess the emergent effects of the nonlinear self interaction in each subsystem.…”
mentioning
confidence: 99%
“…To analyse this, it is convenient to discuss thoroughly the approximations that led into Eq. (16). The separation of timescales that justifies the averaging requires that the resulting effective dynamics does not occur at a rate comparable to the fast timescale.…”
Section: Resultsmentioning
confidence: 99%
“…The small coupling strength near the resonant regime has also been thoroughly investigated, resulting in the integrable Tavis-Cummings model [14] after performing a rotating-wave approximation. Several studies of the dynamics have been done with a variety of motivations, e.g., entanglement, collapses and revivals [15,16], behavior near the classical limit [17], and open system problems [18]. The dynamics in the small qubit frequency regime has also been explored [15], but mainly for low coupling strengths.…”
Section: Introductionmentioning
confidence: 99%